Problematika Administrasi dan Manajemen Sekolah Dasar: Kajian Konseptual dan Implikasi Praktis - Miftahul Jannah; Pitria Lestari Simanjuntak; Melyana Novi Anggi Manalu; Mutiya Arninda Hasibuan; Aldino; Rahmilawati Ritonga (Jurnal Riset Multidisiplin Edukasi, 2025)
School administration and management are strategic components in supporting the quality of primary education. However, many primary schools in Indonesia still face various obstacles in administration and management, ranging from weak documentation to ineffective leadership. These problems have a direct impact on operational efficiency and the quality of education services. This research used a descriptive qualitative approach with data collection techniques through semi-structured interviews, non-participatory observation and documentation studies. The research locations included several public and private primary schools in Medan City, with the main informants consisting of principals, teachers and administrative staff. Data analysis was conducted using the interactive model of Miles and Saldana which includes data reduction, data presentation, and thematic conclusion drawing. The results showed that the main obstacle in school administration lies in the use of manual systems that hinder accuracy and efficiency. On the other hand, principals' managerial competencies are still limited, especially in strategic planning and data-based decision making. The low utilization of information technology and weak internal coordination also worsen the effectiveness of school governance. These problems are systemic and interrelated. The study concludes that primary school administration and management reform needs to be integrated, emphasizing human resource training, system digitalization and cross-role collaboration. The findings make a theoretical contribution to the development of data- and practice-based school management models and are relevant as a policy basis for improving the quality of primary education in Indonesia.